The Slow Wallerian Degeneration Protein, Wld(S), Binds Directly to VCP/p97 and Partially Redistributes It within the Nucleus - Laser, Heike (The American Society for Cell Biology, 2006)
Slow Wallerian degeneration (Wld(S)) mutant mice express a chimeric nuclear protein that protects sick or injured axons from degeneration. The C-terminal region, derived from NAD(+) synthesizing enzyme Nmnat1, is reported to confer neuroprotection in vitro. However, an additional role for the N-terminal 70 amino acids (N70), derived from multiubiquitination factor Ube4b, has not been excluded. In wild-type Ube4b, N70 is part of a sequence essential for ubiquitination activity but its role is not understood. We report direct binding of N70 to valosin-containing protein (VCP; p97/Cdc48), a protein with diverse cellular roles including a pivotal role in the ubiquitin proteasome system. Interaction with Wld(S) targets VCP to discrete intranuclear foci where ubiquitin epitopes can also accumulate. Wld(S) lacking its N-terminal 16 amino acids (N16) neither binds nor redistributes VCP, but continues to accumulate in intranuclear foci, targeting its intrinsic NAD(+) synthesis activity to these same foci. Wild-type Ube4b also requires N16 to bind VCP, despite a more C-terminal binding site in invertebrate orthologues. We conclude that N-terminal sequences of Wld(S) protein influence the intranuclear location of both ubiquitin proteasome and NAD(+) synthesis machinery and that an evolutionary recent sequence mediates binding of mammalian Ube4b to VCP.